Spread McLuhan: theories, concepts, technologis and ruptures - Morais, Osvando de [UNESP] (Univ Santiago Compostela, 2020)
In the McLuhan way, fundamental concepts like the media as extension of man and the medium is the message are more than a revolution. There are synthesis and ruptures. Traces from a technological revolution caught in that context, mid 20th Century. The last McLuhan's conferences and interviews show other face so important of this thinker, true diagnoses of the difficulties of dealing with a universe like the author's. Above all its avant-garde sensibility applied to the unfolding media still in systematization processes. His ideas had the ability to upgrade and also to absorb the continuous, constant and fluid changes. The last conferences and interviews are full of subjective manifestations and subtle ironies that outline an original theory. This paper seeks to outline the main concepts so that the essential as conducting and catalyzing process can be extracted from their theories about the immediates of central nervous system technology. Finally the various senses of McLuhan's thought are supported by Philosophy, Anthropology and Literature, present in the update of the concept of extension, either as an artificial organ, as a prolongation or as am instrument. It's important not to forget the ambiguities of the speeches that show other dimensions of an unseen McLuhan.
Keywords: Marshall McLuhan; media; medium and message; extension; cultura; philosophy